Beyond Individual Differences in Affective Symptomatology: The Distinct Contributions of Emotional Competence and Rumination in a Nationally Representative Sample - Ruth Castillo-Gualda; Juan Ramos-Cejudo (Behavioral Sciences)
Prior evidence suggests mental health, and affective symptomatology in particular, are influenced by emotion-related abilities. The strategies people use to identify, understand, and manage their emotions can serve as a protective or vulnerability factor for their psychological adjustment. Adaptive emotion regulation strategies, such as the ability to identify and understand emotions, can mitigate anxiety and depression symptoms, whereas maladaptive strategies, such as rumination, contribute to the vulnerability to suffering emotional symptomatology. To better understand the role of each strategy in affective outcomes, this study examines the role of adaptive emotion regulation strategies on anxiety, depression, and well-being, in comparison to rumination, among the general population. We hypothesize that the ability to accurately identify emotions and understand inner thoughts will act as protective factors against depression and anxiety, considering neuroticism. In comparison, rumination reactions, such as passively overthinking about inner experiences, will exacerbate the affective symptomatology. A sample of 1703 participants over the country, 50.43% female (18–75 years of age, mean = 45.48, SD = 14.73), closely aligned with the mean age of the target population in Spain, which is 44.1 years, were randomly selected to participate in this cross-sectional study. Participants completed self-report measures for emotional competence, rumination, anxiety and depression symptoms, well-being, and neuroticism. Structural equation modeling (SEM) was used to explore the relationships among the above-mentioned variables. Our results revealed neuroticism is related to higher levels of anxiety and depression and negatively related to wellbeing through the mediation effect of rumination and emotional competence, including all possible paths of the mediation model. This study has important implications for designing preventive and therapeutical interventions.